OPTIMIZING THE DISTRIBUTION OF ZAKAT, INFAQ, SHADAQA (ZIS) THROUGH THE BAZNAS PROGRAM ON PROSPERITY LEVELS IN BENGKALIS - Trisna Eka Sari; Seri Wahyuni; Riskiyatul Hasanah; Khaeqal Fitradinata (CV SWA Anugrah, 2023)
Social prosperity is a priority scale in efforts to achieve national development. Until now, the country is still facing problems and difficulties in achieving social prosperity. The Bengkalis Regency said that there was a problem with the high number of people below the poverty line. He said that